Descriptive analysis of immunological abnormalities in recurrent reproductive failure and therapeutical outcomes - Eduardo de la Fuente-Muñoz; Nabil Subhi-Issa; Ángela Villegas Mendiola; Juliana Ochoa-Grullón; Kissy Guevara-Hoyer; Raquel Gil-Laborda; Lydia Pilar-Suárez; María Dolores Mansilla Ruíz; María Pilar Gasca Escorial; Teresa Gastañaga-Holguera; Marta Calvo Urrutia; María Guzmán Fulgencio; et al. (Medwave)
Introduction Reproductive immunology has advanced significantly, recognizing the immune system as crucial in pregnancy development and facilitating the identification of abnormalities causing recurrent reproductive failure, as well as proposing targeted treatments for these patients.